On the Variation of Hedging Decisions in Daily Currency Risk Management - Charles S. Bos; Ronald J. Mahieu; Herman K. van Dijk (Tinbergen Institute, 2001)
Internationally operating firrns naturally face the decision whether or not to hedge the currencyrisk implied by foreign investments. In a recent paper, Bos, Mahieu and van Dijk (2000) evaluatethe returns from optimal and alternative currency hedging strategies, for a series of 7 models,using Bayesian inference and decision analysis. The models differ in the way time-varying means,variances or the unconditional error distributions are incorporated. In this extension, we comparethe hedging decisions and financial returns and utilities as they result from the modellingassumptions and the attitudes towards risk.
Keywords: C11; C44; E47; G15; 330; Exchange rates; risk management; Bayesian analysis; Hedging; Währungsderivat; Risikomanagement; Theorie